Griffiths phase, magnetic memory and ac susceptibility of an antiferromagnetic titanate-based perovskite Er0.9Sr0.1Ti0.975Cr0.025O3 system. (2nd April 2020) - Hamdi, R; Smari, M; Bajorek, A; Bessais, L; Dhahri, E; Samara, A; Mansour, S A; Haik, Y
Abstract: In this study, we investigated different physical properties of Er0.9 Sr0.1 Ti0.975 Cr0.025 O3 titanate prepared by a solid-state reaction that produces a cubic structure with Fd-3m (227) as a space group. Zero-Field Cooled and Field Cooled measurements show a second-order antiferromagnetic transition at Neel temperature TN  = 23 K, and the existence of Griffiths phase at around TGP  = 132 K. This soft magnetic material depicts a magnetic memory since it 'remembers' its thermal history. The relative cooling power of this titanate-based sample was then measured to be around 292.27 J kg −1 at 5 Tesla and 400 J kg −1 at 6 Tesla. However, these values are lower than the RCP value reported for the most magnetic refrigerant Gd, although these results are high enough compared to different perovskite systems. Therefore, Er0.9 Sr0.1 Ti0.975 Cr0.025 O3 is a very suitable, environment-friendly magnetic refrigerant.